2017
DOI: 10.2174/1385272821666170111151917
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Properties of 2(5H)-Furanones Featuring Bromine Atoms on the Heterocyclic Ring and/or Brominated Substituents

Abstract: This review deals with the synthesis of unnatural and natural 2(5H)-furanone derivatives featuring bromine atoms on the heterocyclic ring and/or brominated substituents, which have been described in the literature since 1951 up to February 2016. The review has been organized on the basis of six classes of brominated furanone derivatives that were synthesized: i) 2(5H)-furanone derivatives with one bromine atom on the heterocyclic ring; ii) 2(5H)-furanone derivatives with two bromine atoms on the heterocyclic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 209 publications
0
12
0
Order By: Relevance
“…Due to good reactivity and biological activity of 2(5 H )‐furanone compounds, the design and synthesis of 2(5 H )‐furanone‐based drugs have attracted chemist's research interests . In our previous research, we reported a series of 4‐benzidino‐2(5 H )‐furanones 3 (Scheme 1) with acceptable antiproliferative activity against breast cancer cell [15c].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to good reactivity and biological activity of 2(5 H )‐furanone compounds, the design and synthesis of 2(5 H )‐furanone‐based drugs have attracted chemist's research interests . In our previous research, we reported a series of 4‐benzidino‐2(5 H )‐furanones 3 (Scheme 1) with acceptable antiproliferative activity against breast cancer cell [15c].…”
Section: Resultsmentioning
confidence: 99%
“…2(5 H )‐Furanone is present in a large number of biologically active compounds, including natural products and pharmaceutical agents . In the field of medicinal chemistry, halogenated 2(5 H )‐furanone derivatives have always received considerable attention because of their biological importance and synthetic feasibility . In particular, 4‐arylamino‐2(5 H )‐furanone scaffold is considered as an important template for the development of new drugs .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the natural ( Z )-4-bromo-5(bromomethylene)-2( 5H )-furanone-C30 has been extensively studied and recent studies showed that this compound is able to bind to LuxR type protein such as LasR and RhlR in pseudomonas aeruginosa [ 57 ]. In 2017, Fabio Bellina and co-workers described a state of the art of the chemistry of furanones and their relevant bioactivity [ 58 ]. Below we give an update on the furanone type compounds with examples reported since, and with compounds with similar structures.…”
Section: Non-ahl Related Heterocyclic Compounds With Ahl-like Qs Activitymentioning
confidence: 99%
“…2(5H)-furanone ($18/g, purity: 98%, 2019) has high biological activities; hence, it is widely used for antibacterial, anti-inflammatory, antiviral, and anti-cancer applications. In addition, 2(5H)-furanone has been shown to be a suitable starting point to synthesize medicinal and industrial products in recent years (Li et al 2016;Rossi et al 2017).…”
Section: Introductionmentioning
confidence: 99%